Organizational Framework Development: Formulating Strategy to Increase Digital Maturity - Maharanie Anggun Kurniya; Made Andriani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This paper aims to develop an organizational framework for formulating a strategy to increase digital maturity. The research stages consist of: (1) Problem observation, (2) Literature review, (3) Model development, (4) Discussion, and (5) Conclusion. Specifically, the model development stage becomes this research's findings and originality. The results show that the organizational framework proposed in this research can help companies formulate strategies from operational business processes through a structured and systematic organizational framework. This framework consists of four systematic steps: (1) digital maturity assessment, (2) business process mapping, (3) business process characteristic identification, and (4) strategy formulation. Also, the strategy that arises by implementing the proposed organizational framework is obvious and structured because the resulting strategy considers business processes' characteristics. Specifically, this research suggests that the company may develop a web-based knowledge-sharing community for externalizing tacit knowledge into explicit knowledge to solve tacit knowledge needs to be managed. The research does not discuss the suggestion to develop a web-based knowledge-sharing community as a strategy's practical implication in detail. Also, considering the web-based knowledge-sharing community is a strategy designed in this case based on the characteristics and knowledge needs of prioritized business processes, the strategy formulation needs adjustment if the business process has turned into different characteristics. The organizational framework for formulating a strategy to increase digital maturity from the operational business process point of view has not been investigated previously.